Perspectives on team cognition and team sports - McNeese, N.; Cooke, N. J.; Fedele, M.; Gray, R. (Sport and exercise psychology research: From theory to practice, 2016)
Sports are an important aspect of almost every culture and have also helped to define what most people consider a team. Like sports, teams permeate society. Teamwork that occurs within sports teams generally consists of physical coordination and cognitive processing. The interaction between physical coordination and cognitive processing at the team level or team cognition drives teamwork. Team cognition is a rich research area, yet studies of team cognition and team sports have been minimal. Team cognition has been studied from one of two different perspectives: information processing/shared knowledge and ecological. Though each perspective is useful, most research on team cognition work has taken the information processing/shared knowledge approach. In this chapter, we review each perspective, and assess each in regards to the context of team sports. We conclude by recommending an integrative perspective, utilizing aspects of both team cognition perspectives, to study team cognition during team sports. (übern.)